Collards—Brassica oleracea L. (Acephala group) - James M. Stephens (EDIS)
This document provides an overview of collards (Brassica oleracea L., Acephala group), a leafy green vegetable commonly grown in Florida and other southern states. It details the plant’s characteristics, cultivation practices, preferred growing conditions, common pests and diseases, and harvesting methods. Collards thrive in cooler months and are valued for their nutritional leaves, often cooked as greens. The document also highlights recommended varieties, including ‘Georgia’ and ‘Vates,’ and offers guidance on soil preparation and pest control to optimize yield and quality. Original publication date May 1994.